Hot electrons in a nanowire hard X-ray detector - Zapf, Maximilian; Ritzer, Maurizio; Liborius, Lisa; Johannes, Andreas; Hafermann, Martin; Schoenherr, Sven; Segura-Ruiz, Jaime; Martinez-Criado, Gema; Prost, Werner; Ronning, Carsten (Nature Communications, 2020)
Nanowire chip-based electrical and optical devices such as biochemical sensors, physical detectors, or light emitters combine outstanding functionality with a small footprint, reducing expensive material and energy consumption. The core functionality of many nanowire-based devices is embedded in their p-n junctions. To fully unleash their potential, such nanowire-based devices require – besides a high performance – stability and reliability. Here, we report on an axial p-n junction GaAs nanowire X-ray detector that enables ultra-high spatial resolution ( 200 nm) compared to micron scale conventional ones. In-operando X-ray analytical techniques based on a focused synchrotron X-ray nanobeam allow probing the internal electrical field and observing hot electron effects at the nanoscale. Finally, we study device stability and find a selective hot electron induced oxidization in the n-doped segment of the p-n junction. Our findings demonstrate capabilities and limitations of p-n junction nanowires, providing insight for further improvement and eventual integration into on-chip devices.
CRIS-Team Scopus Importer:2023-04-20